Association Between Utilization of Quitline Services and Probability of Tobacco Abstinence in Low-Income Smokers - Bernstein, Steven L. (J Subst Abuse Treat, 2016)
INTRODUCTION: Quitlines (QL) are an effective means for smoking cessation, but a paucity of data exist examining the dose-response relationship between use of QL services and quit rates, especially among low-income smokers. The purpose of this study was to study the relationship between tobacco abstinence and use of QL services among low-income smokers. METHODS: Secondary analysis of a randomized trial of every- or some-day smokers age 18 years or older visiting an urban Emergency Department. Inclusion criteria included self-pay or Medicaid insurance, as a proxy for low-income and low socioeconomic status. Intervention participants received a motivational interview, 6 weeks of nicotine patches and gum, a referral faxed to the state-sponsored QL, a booster call, and a quitline brochure. Control participants received the brochure. Smoking status was assessed by phone at 1 and 3 months, with confirmation via exhaled carbon monoxide testing at 3 months for those reporting abstinence. QL usage was obtained by utilization data from the QL database. RESULTS: Of 778 subjects, 197 (25.3%) reported any use of QL services at 3 months. Participants were trichotomized: no QL usage, 1 call only, and >1 call (583, 99, and 98 participants, respectively). Quit rates at 3 months in these no, low-, and high-use groups were, respectively, 7.2%, 9.1%, and 15.3% (P=0.03). Participants who used the QL had a median of 28 total minutes of telephone contact. CONCLUSION: Among low-income smokers, greater use of QL services is associated with higher abstinence. Whether this resulted from a direct effect of the QL, or greater motivation among smokers using QL services cannot be determined from these data.